Use of Pineapple Waste as Fuel in Microbial Fuel Cell for the Generation of Bioelectricity - Rojas-Flores, Segundo (2022)
The excessive use of fossil sources for the generation of electrical energy and the increase in different organic wastes have caused great damage to the environment; these problems have promoted new ways of generating electricity in an eco-friendly manner using organic waste. In this sense, this research uses single-chamber microbial fuel cells with zinc and copper as electrodes and pineapple waste as fuel (substrate). Current and voltage peaks of 4.95667 ± 0.54775 mA and 0.99 ± 0.03 V were generated on days 16 and 20, respectively, with the substrate operating at an acid pH of 5.21 ± 0.18 and an electrical conductivity of 145.16 ± 9.86 mS/cm at two degrees Brix. Thus, it was also found that the internal resistance of the cells was 865.845 ± 4.726 Ω, and a maximum power density of 513.99 ± 6.54 mW/m2 was generated at a current density of 6.123 A/m2, and the final FTIR spectrum showed a clear decrease in the initial transmittance peaks. Finally, from the biofilm formed on the anodic electrode, it was possible to molecularly identify the yeast Wickerhamomyces anomalus with 99.82% accuracy. In this way, this research provides a method that companies exporting and importing this fruit may use to generate electrical energy from its waste.